Whose book is it anyway? a view from elsewhere on publishing, copyright and creativity - Jefferies, Janis; Kember, Sarah; CREATe; Open Book Publishers (Open Book Publishers : CREATe, 2019)
"Whose Book is it Anyway? is a provocative collection of essays that opens out the copyright debate to questions of open access, ethics, and creativity. It includes views - such as artist's perspectives, writer's perspectives, feminist, and international perspectives - that are too often marginalized or elided altogether. The diverse range of contributors take various approaches, from the scholarly and the essayistic to the graphic, to explore the future of publishing based on their experiences as publishers, artists, writers and academics. Considering issues such as intellectual property, copyright and comics, digital publishing and remixing, and what it means (not) to say one is an author, these vibrant essays urge us to view central aspects of writing and publishing in a new light. Whose Book is it Anyway? is a timely and varied collection of essays. It asks us to reconceive our understanding of publishing, copyright and open access, and it is essential reading for anyone invested in the future of publishing."--Publisher's website.
Notes on Contributors -- Introduction: Whose Book is it Anyway? A View from Elsewhere on Publishing, Copyright and Creativity / Janis Jefferies and Sarah Kember -- PART I: Opening out the Copyright Debate: Open Access, Ethics and Creativity. ; 1. A Statement by The Readers Project Concerning Contemporary Literary Practice, Digital Mediation, Intellectual Property, and Associated Moral Rights / John Cayley and Daniel C. Howe ; 2. London-Havana Diary: Art Publishing, Sustainability, Free Speech and Free Papers / Louise O'Hare ; 3. The Ethics of Emergent Creativity: Can We Move Beyond Writing as Human Enterprise, Commodity and Innovation? / Janneke Adema ; 4. Are Publishers Worth It? Filtering, Amplification and the Value of Publishing / Michael Bhaskar ; 5. Who Takes Legal Responsibility for Published Work? Why Both an Understanding and Lived Experience of Copyright Are Becoming Increasingly Important to Writers / Alison Baverstock ; 6. Telling Stories or Selling Stories: Writing for Pleasure, Writing for Art or Writing to Get Paid? / Sophie Rochester ; 7. Copyright in the Everyday Practice of Writers / Smita Kheria ; 8. Comics, Copyright and Academic Publishing: The Deluxe Edition / Ronan Deazley and Jason Mathis -- PART II: Views from Elsewhere. 9. Diversity or die: How the Face of Book Publishing Needs to Change if it is to Have a Future / Danuta Kean ; 10. Writing on the Cusp of Becoming Something Else / J. R. Carpenter ; 11. Confronting Authorship, Constructing Practices (How Copyright is Destroying Collective Practice) / Eva Weinmayr ; 12. Ethical Scholarly Publishing Practices, Copyright and Open Access: A View from Ethnomusicology and Anthropology / Muriel Swijghuisen Reigersberg ; 13. Show me the Copy! How Digital Media (Re)Assert Relational Creativity, Complicating Existing Intellectual Property and Publishing Paradigms / Joseph F. Turcotte ; 14. Redefining Reader and Writer, Remixing Copyright: Experimental Publishing at if:book Australia / Simon Groth -- APPENDIX: CREATe Position Papers. 1. Publishing Industry / Janis Jefferies ; 2. Is the Current Copyright Framework fit for Purpose in Relation to Writing, Reading and Publishing in the Digital Age? / Laurence Kaye ; 3. Is the Current Copyright Framework fit for Purpose in Relation to Writing, Reading, and Publishing in the Digital Age? / Richard Mollet ; 4. History of Copyright Changes 1710-2013 / Rachel Calder ; 5. Is the Current Copyright Framework fit for Purpose in Relation to Writing, Reading, and Publishing in the Digital Age? / Max Whitby -- List of Illustrations -- Index.
Available through Open Book Publishers.
Includes index.
Mode of access: World Wide Web.
Keywords: Authorship; Copyright, International; Copyright; Open access publishing; Publishers and publishing